Boom! Excursions in Fantasy Land - Van Loon, Julienne (ABC Books, 2007)
This literary essay explores everyday lived experience during the mining boom in Perth, Western Australia, particularly the idea that the cultural narrative of economic progress obscures and excludes, both imaginatively and geographically, other ways of being.